Creating Healthy Universities: The role of campus‐based health promotion events in supporting student well‐being. (29th November 2019) - Saheb, Rowena; Mortimer, Taylor; Rutherford, Erin; Sperandei, Sandro; Reis, Arianne
Abstract: Issue addressed: University students have been increasingly recognised as a population with a high prevalence of mental ill health, with research suggesting that psychological distress is higher among tertiary education students than nonstudents. The purpose of this study was to assess students' perceptions of the effectiveness of student‐led, campus‐based mental health promotion events on their well‐being. Methods: The cross‐sectional study included six campus‐based events, and collected data from 700 university students using a survey tool that included quantitative and qualitative measures. A multivariate logistic regression model was developed to investigate the association among explanatory variables and the response variable. A log‐likelihood ratio test was used to assess the goodness of fitness of the final model. Qualitative data were thematically analysed. Results: Results showed that the majority of students (84%) agreed the event promoted and supported student well‐being, with three variables being statistically related to this agreement: (a) respondents' decision to spend more time on campus due to the event; (b) how respondents felt about receiving health information from student peers; and (c) the number of activities in which they took part. Conclusions: Our findings suggest that campus‐based mental health promotion events need to be designed with emphasis on activities that attract, retain and educate students about mental health, and are delivered with the benefits of peer‐to‐peer health promotion in mind, in order to reach their full potential in supporting improved student mental health. So what?: The findings highlight the opportunities that can be created by university events to promote and support student mental health by building peer relationships and creating a sense of community. Summary: The purpose of the study was to assess students' perceptions (n = 700) of the effectiveness of student‐led, campus‐based mental health promotion events on well‐being. Findings highlight the opportunities that can be created by university events to promote and support student mental health by building peer relationships and creating a sense of community.